Fostering Self-Efficacy in English Speaking among Canossian Sisters: Challenges and Strategies - FdCC, Sr. Natalina Antónia dos Santos; Sanjaya, Paschalis Kurniawan; Mbato, Concilianus Laos (Journal of English Teaching, Literature, and Applied Linguistics, 2025)
This study explores the self-efficacy of Canossian Sisters in speaking English, focusing on their perceived challenges and the support they receive within their religious community. Grounded in Bandura’s Self-Efficacy Theory and using a phenomenological approach, the study involved in-depth interviews and observations with five Canossian sisters from diverse linguistic backgrounds. Findings revealed three key themes: 1) the importance of English in global and mission-related contexts, 2) communication challenges, particularly pronunciation, vocabulary, and confidence, and 3) strategies to improve English, such as listening to songs and engaging with English-speaking communities, and positive feedback from environment. The results underscore that supportive learning environments and consistent practice play pivotal roles in enhancing self-efficacy. The study highlights the need for tailored formative strategies in religious communities to build confidence in EFL communication, especially in multicultural and multilingual settings. These insights contribute to the development of educational interventions that empower religious learners to effectively communicate in English, aligning with their vocational missions.